A General Perspective of Big Data Analytics: Algorithms, Tools and Techniques - P, Pandeeswary; M, Janaki (International Journal of Computer Sciences and Engineering, 2019)
Big data is the term representing any collection of datasets so large and complex which is difficult to process using traditional data processing applications. The challenges comprise of analysis, capture, search, sharing, storage, transfer, visualization, and privacy violations. Big data is a set of techniques and technologies that need new forms of integration to uncover large hidden values from large datasets which is diverse, complex, and of a massive scale. Big data environment is used to acquire, organize and analyze a variety of data. The main objective of this paper is to give a general perspective of big data analytics, its process, tools and techniques used. There is an immense need for the construction of algorithms to handle Big Data. Many algorithms are defined in the analysis of large data set. A review of various techniques and algorithms are also discussed in this paper. The massive volume of both structured and unstructured data which is so large, it is difficult to gather and analyze for getting the required solution. It is better to have some tools which help in processing the complex data sets. This paper is also focused on various tools available to extract required data from big data.